2006
DOI: 10.1007/s11069-006-0001-2
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Amplification Effects in Fault Zone Related to Rock Mass Jointing

Abstract: Results of geological, geomechanical and seismometric investigations aiming at the analysis of the seismic response in a carbonate ridge of the Nera River valley (Central Apennines -Italy) are discussed. Geological and geomechanical surveys were aimed at defining the stratigraphic and structural setting of the outcropping formations and the jointing conditions of the rock mass. Velocimetric records of both ambient noise and small-magnitude earthquakes were analysed in order to identify amplification conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…23 illustrates for the Canadian landslides described in this paper how the rock mass structure and discontinuity surface conditions are degraded as the zones associated with tectonic damage move downward and to the right in the GSI table. Recent work by Martino et al (2006) also found that rock mass quality as quantified by the number of discontinuities per unit volume increased and the average size of the rock block decreased near faults. They also found the seismic amplification can occur in fault zones if there is a sharp contrast in rock mass quality between the background rock mass and the fault zone (Martino et al, 2006).…”
Section: Rock Mass Quality and The Influence Of Tectonic Structures Omentioning
confidence: 91%
“…23 illustrates for the Canadian landslides described in this paper how the rock mass structure and discontinuity surface conditions are degraded as the zones associated with tectonic damage move downward and to the right in the GSI table. Recent work by Martino et al (2006) also found that rock mass quality as quantified by the number of discontinuities per unit volume increased and the average size of the rock block decreased near faults. They also found the seismic amplification can occur in fault zones if there is a sharp contrast in rock mass quality between the background rock mass and the fault zone (Martino et al, 2006).…”
Section: Rock Mass Quality and The Influence Of Tectonic Structures Omentioning
confidence: 91%
“…valley effects (Semblat et al 2005;Pagliaroli et al 2014 among others), a satisfactory understanding of topography effects, especially from a quantitative point of view, has not yet been achieved (Pagliaroli et al 2011). This is essentially because of the intertwining of effects related to local morphology with those associated to stratigraphic features (e.g., soft debris aprons resting on rocks), near surface weathering (LeBrun et al 1999) and complex structural heterogeneities (e.g., pervasive fracturing) generally due to the presence of fault zones (Rovelli et al 2002;Martino et al 2006). The latter aspect has been specifically investigated by Marzorati et al (2011), who highlighted the primary influence of rock mass condition (orientation and opening of fractures and joints) on ground motion amplification along rocky ridges, where site effects are generally supposed to be related to ''canonical'' morphological/topographic issues.…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades some workers Vidale et al, 1991;Spudich et al, 1996;Xu et al, 1996;Martino et al, 2006) have reported cases of notable directional variations of seismic site response under different geological and topographical conditions. Our recent studies provided new evidence of this phenomenon (Del Gaudio and Wasowski, 2007).…”
Section: Introductionmentioning
confidence: 99%